2020
DOI: 10.4254/wjh.v12.i10.738
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma Liver Imaging Reporting and Data Systems treatment response assessment: Lessons learned and future directions

Abstract: Hepatocellular carcinoma (HCC) is a leading cause of morbidity and mortality worldwide, with rising clinical and economic burden as incidence increases. There are a multitude of evolving treatment options, including locoregional therapies which can be used alone, in combination with each other, or in combination with systemic therapy. These treatment options have shown to be effective in achieving remission, controlling tumor progression, improving disease free and overall survival in patients who cannot under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…The LR-TR was primarily designed to increase inter-reader agreement in reporting and improve decision-making processes (Voizard et al 2019a ). It is a relatively new algorithm that offers new opportunities to further improve HCC patient care, but still requires in-depth research (Aslam et al 2020b ; Do and Mendiratta-Lala 2020 ). Previous studies have shown that tumor response after TACE (assessed using the mRECIST or WHO criteria) is associated with patient outcomes/overall survival (Shim et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The LR-TR was primarily designed to increase inter-reader agreement in reporting and improve decision-making processes (Voizard et al 2019a ). It is a relatively new algorithm that offers new opportunities to further improve HCC patient care, but still requires in-depth research (Aslam et al 2020b ; Do and Mendiratta-Lala 2020 ). Previous studies have shown that tumor response after TACE (assessed using the mRECIST or WHO criteria) is associated with patient outcomes/overall survival (Shim et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…After treatment, it is important to assess tumor response to determine further management, patient prognosis, and endpoint outcomes for clinical trials. Histopathologic changes within the post-radiation treatment bed are well characterized [26,27] , although histologic assessment of response with follow-up biopsy in clinical practice is not feasible. Imaging, aided or not by clinical and laboratory data (e.g., Alphafetoprotein levels), is the most used method to assess changes in tumor burden as a predictor of treatment response.…”
Section: Assessment Of Response To Treatmentmentioning
confidence: 99%
“…Additionally, Liver Imaging Reporting and Data Systems (LI-RADS) Treatment Response Algorithm (TRA) has been conceived to offer a standardized evaluation of HCC following loco regional therapy (LRT). LI-RADS TRA offers a step-by-step method to assess each nodule individually for precise treatment evaluation [ 20 ]. Although the adoption of imaging tool (computed tomography (CT) or magnetic resonance imaging (MRI)) can be subject to patient characteristics and institutional inclination, it is critical to maintain consistency in the imaging performed before and after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although the adoption of imaging tool (computed tomography (CT) or magnetic resonance imaging (MRI)) can be subject to patient characteristics and institutional inclination, it is critical to maintain consistency in the imaging performed before and after treatment. Precise assessment of post-treatment imaging is critical to guide further management decisions and requires comparison of post- treatment with pre-treatment imaging to recognize the original lesion diameter and enhancement features [ 20 ]. Follow-up imaging of patients with treated HCC is performed to evaluate for new lesions, monitor for evidence of early recurrence and observe for neovascularity that may allow for detection of pathological angiogenesis within the ablation zone.…”
Section: Introductionmentioning
confidence: 99%